Green Synthesis, Biological Evaluation of Newer Benzothiazole Derivatives (Journal of Basic and Applied Research in Biomedicine, 2022)
Benzothiazole is one of the most important heterocyclic compound, weak base, having varied biological activities and still of great scientific interest now a days. They are widely found in bioorganic and medicinal chemistry with application in drug discovery. In the present study some novel benzothiazole derivatives were synthesized under green synthesis by microwave irradiation method by using Phenyliodoniumbis-trifluoroacetate (PIFA) in ethanol according to the scheme. All the synthesized benzothiazole derivatives have been characterized by using elemental analysis, FT-IR, 1HNMR, 13C NMR spectroscopy and further supported by mass spectroscopy. Purity of all the compounds has been checked on thin layer chromatographic plate and HPLC technique. All the synthesized compounds were evaluated for antimicrobial activity by estimating the minimum inhibitory concentration (MIC) by adopting serial dilution technique and analgesic activity was examined by using the hot-plate method. All the compounds exhibited moderate to significant antimicrobial and analgesic activities.